Parasitic copepods of the family Lernanthropidae Kabata, 1979 (Copepoda: Siphonostomatoida) from Australian fishes, with descriptions of seven new species - Boxshall, Geoff A.; Bernot, James P.; Barton, Diane P.; Diggles, Ben K.; Yong, Russell Q-Y.; Atkinson-Coyle, Toby; Hutson, Kate S. (Zootaxa, 2020)
The total number of species of Lernanthropidae previously recorded from Australian waters is 15 (i.e., one species each of Aethon Krøyer, 1837, Lernanthropodes Bere, 1936, and Lernanthropsis Do, in Ho & Do, 1985; 10 species of Lernanthropus de Blainville, 1822; and two species of Sagum Wilson, 1913), and all of these records are reviewed. We report here the presence of three species of Aethon. One species, A. garricki Hewitt, 1968, is reported from Australian waters for the first time and a new species, A. bicamera sp. nov., is described from the latrid, Latris lineatus (Forster, 1801) caught off South Australia. The genus Lernanthropodes is represented by a single species, L. trachinoti Pillai, 1962. We recognize Chauvanium Kazachenko, Kovaleva, Nguyen & Ngo, 2017 as a subjective synonym of Lernanthropodes and transfer its type and only species C. chauvani Kazachenko, Kovaleva, Nguyen & Ngo, 2017 which becomes Lernanthropodes chauvani (Kazachenko, Kovaleva, Nguyen & Ngo, 2017) n. comb. Lernanthropsis mugilii (Shishido, 1898) is reported here from Mugil cephalus Linnaeus, 1758 sampled in Queensland and in New South Wales. The genus Lernanthropus is the most species rich and we report the presence of 20 nominal species on Australian marine fishes. This total includes six new species: L. alepicolus sp. nov. from Alepes apercna Grant, 1987, L. elegans sp. nov. from Atractoscion aequidens (Cuvier, 1830), L. gnathanodontus sp. nov. from Gnathanodon speciosus (Forsskål, 1775), L. paracruciatus sp. nov. from Protonibea diacanthus (Lacepède, 1802), L. pemphericola sp. nov. from Pempheris compressa (White, 1790), and L. selenotoca sp. nov. from Selenotoca multifasciata (Richardson, 1846). In addition, we report the presence of another four species in Australian waters for the first time: L. abitocephalus Tripathi, 1962, L. cadenati Delamare Deboutteville & Nuñes-Ruivo, 1954, L. microlamini Hewitt, 1968, and L. pomadasysis Rangnekar & Murti, 1961. After reexamination of the types of L. paenulatus Wilson, 1922 held in the USNM, we relegate this species to subjective synonymy with L. seriolii Shishido, 1898. Previous records of L. paenulatus from Australian Seriola species should be reassigned to L. seriolii. Lernanthropus ecclesi Kensley & Grindley, 1973 is recognized as a junior subjective synonym of L. micropterygis Richiardi, 1884, and L. delamarei Marques, 1960, which is based on the male only, is tentatively considered to be a junior subjective synonym of L. micropterygis. Males are described for the first time for three species; L. breviculus Kabata, 1979, L. microlamini and L. mollis Kabata, 1979. A member of the genus Mitrapus Song & Chen, 1976, M. oblongus (Pillai, 1964), is reported from Australia for the first time, on Herklotsichthys castelnaui (Ogilby, 1897) caught off Queensland and New South Wales. Finally, two species of Sagum were previously known from Australia and here we add three more. Two of the newly reported species were originally described as species of Lernanthropus but we formally transfer them here to Sagum as S. lativentris (Heller, 1865) n. comb. and S. sanguineus (Song, in Song & Chen, 1976) n. comb. The males of S. lativentris and S. vespertilio Kabata, 1979 are described for the first time. A key to the females of the 31 species of lernanthropids found in Australian waters is provided.